Pengembangan Sistem Peringatan Dini Bencana Banjir Lahar Hujan Merapi di Sungai Blongkeng Kabupaten Magelang - Agung Yulianto Nugroho; Awang Hendrianto Pratomo; Eko Teguh Paripurno; Johan Danu Prasetya; Arif Rianto Budi Nugroho; Ficky Adi Kurniawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Mount Merapi is one of the most active volcanoes in Indonesia and is located in the Sleman Regency area of the Special Region of Yogyakarta Province and the Magelang, Klaten and Boyolali Regencies in Central Java Province. There are tools to support the early warning system located at stations or posts around the Blongkeng River. This tool is still active and is needed to notify you if a rain lava flood disaster will occur with a water level sensor. Therefore, a warning system model is needed that can be utilized by the community around Blongkeng. This research was conducted using qualitative methods with data obtained through FGD/Interviews, Observation and documentation studies. The subjects of this research were 15 residents living around the Blongkeng River. The research results show that the existing device developed can provide information to the people around Blongkeng if the water level is dangerous and has the potential for lava flooding. From the results of interviews, observations and documentation studies, it shows that the community needs tools and systems to receive early warnings when a rain lava flood disaster occurs. Furthermore, as a means of information for villages located on the top/slopes of Mount Merapi to be able to provide information to villages located below it when lava floods will occur. Existing devices can provide information to people living around the Blongkeng River if the water level is dangerous and has the potential for rain lava flooding, although there are still several obstacles because there are tools at the Salamsari Station/Post that need to be calibrated.